The Comparative Advantages of "the Economic Zone on the West Shore of the Taiwan Strait" among the Southeast Coast Cities of China and its Development Strategies - Ziye Na; Yifeng Yao (European Regional Science Association (ERSA), 2012)
The "Economic Zone on the West Shore of the Taiwan Strait" (WSTS) is a concept proposed by government of Fujian Province in 2004 and got the approval by the Chinese national government in 2009, and its development plan was officially published in March 2011. It is a region that cross the administrative boundaries - it is composed by the whole Fujian Province, 3 municipalities of Zhejiang Province, 4 municipalities of Jiangxi Province and 4 municipalities of Guangdong Province. This region gets its name because it is the part of mainland China that is nearest to Taiwan, and the region basically share the same culture and dialect with Taiwan. The main functions were designed to be "the pioneer stage of Taiwan-Mainland China cooperation, the places that serve as new gateways, the places that undertake the advanced manufacturing industries from/as Taiwan, and the new natural and cultural tourist center of China". Actually if considering the economies of Yangtze River delta to its north, the Pearl River Delta to its south and Taiwan to its east (its west sides are mountains), this region seems to be the economic lowlands of southeast coast of China. Relatively, its infrastructure, technology and talents present comparative disadvantages. Due to the development of transportation and information technology, the physical vicinity does not seem to be an advantage, thus "the pioneer stage of Taiwan-Mainland China cooperation and the area to undertake the moving out industries of Taiwan" in the development strategies seem inconvincible. The paper aims to rethink the comparative advantages of WSTS within the "territory cohesion" scheme - territory efficiency, territory quality and territory identity. The dimensions of "economic geography, economic performance, resource efficiency, internal and external accessibility, environment, access to knowledge, presence of ®social capital; landscape and cultural heritage", and also the policies that aim to attract the investors/inhabitants will be considered all over the main cities of the southeast coast of China. Through these reconsiderations, the comparative advantages and the position of this region in the city network of southeast China could be clear and its development strategies could be concluded.
Keywords: 330